Efficacy and safety of intercostal nerve anastomosis in immediate subpectoral prosthetic breast reconstruction after nipple–areola-sparing mastectomy: a randomized, controlled, open-label clinical study - Juan, Zhang; Liang, Yong-Ping; Shen, Jiang-Lun; Dai, Hao; Zhang, Yang; Yao, De-Shun; Jiang, Run-Xue; Cai, Hai-Feng (Frontiers in Oncology, 2024)
Purpose: To investigate the efficacy and safety of intercostal nerve anastomosis among breast cancer patients undergo immediate postpectoral prosthetic breast reconstruction after nipple-areola-sparing mastectomy. Methods: From 2022 to 2023, female patients aged from 20 to 60, diagnosed with stage I-IIIA breast cancer, required and were willing to undergo immediate postpectoral prosthetic breast reconstruction after nipple-areola-sparing mastectomy, were screened and assigned to take the operation with (treatment group) or without (control group) intercostal nerve anastomosis (the nerves with appropriate length and thickness were selected from the 2nd-4th intercostal nerves, which were then dissociated and anastomosed to the posterior areola tissue). All surgical incisions were radial incisions on the surface of the tumor. The patients' breast local sensation was assessed using Semmes-Weinstein monofilaments pre-operatively, 10 days, 3 months, and 6 months postoperatively. Patients' quality of life was evaluated 6 months postoperatively using the EORTC QLQ-C30 questionnaire. Adverse events, operation duration, drainage volume, and the duration of drainage tube carrying time were monitored and recorded. Results: Compared to the pre-operative period, a significant decrease in local sensation was observed 10 days after surgery in both of the two groups. However, the control group showed a significant reduction in sensation at 3 months and 6 months postoperatively, while the treatment group showed noticeable recovery. A statistically significant difference (P<0.001) in local sensation between pre-operative and post-operative was observed at the final follow-up in the two groups. By the time of 3 months and 6 months postoperatively, a significant difference was seen in the local sensation between the two groups. Intercostal nerve anastomosis was found to significantly improve the patients' quality of life, including emotional (P=0.01), physical (P=0.04), social functioning (P=0.02), and pain (P=0.04). There were no significant differences in general characteristics (such as age, BMI, subtypes). Although intercostal nerve anastomosis increased the duration of operation by around 20 minutes (P<0.001), it didn’t affect the volume or duration of postoperative drainage tube usage between the two groups. Conclusion: This study indicated that intercostal nerve anastomosis improved the local sensation and quality of life of patients who underwent immediate postpectoral prosthetic breast reconstruction after nipple-areola-sparing mastectomy.